New Data on Threatened Lepidopterofauna of North-Eastern Albania - LaÃ§ej, Ariana Striniqi; Misja, Kastriot (Mediterranean Journal of Social Sciences, 2012)
Butterflies represent an interesting group of insects with a high diversity. Preserving the value of this diversity requirescontinuous monitoring, especially of endangered and threatened species. In this paper I am going to present some North-EasternAlbania Lepidoptera species that are endangered in their habitats and have their threatened categories at the national level based on theRed List of IUCN (International Union for the Protection of Nature). There are exactly 28 butterfly species with their risked categories,from different regions of North-Eastern Albania, that belong respectively to IUCN categories: DD (4 species), EN (2 species), LR (1specie), CR (2 species), VU (19 species). For each type are given for the venue, habitat, chorology, and also are givenideas about the causes of risk and protective measures.